Tuberculosiss Arthritis: A Case Report - Anak Agung Gede Ocha Rama Kharisma Putra1 , Ni Wayan Candrawati2 , Ida Bagus Ngurah Rai2 (Institute of Medico-legal Publications Pvt Ltd, 2021)
Tuberculosis Arthritis of the knee joint is rare. A 25-year old female patient presented with pain andswelling of her left knee. The symptoms first appeared two months earlier; she was given glucocorticoidafter diagnosed with Rheumatoid Arthritis. The patient did not improve with the treatment. The patient wasdiagnosed with tuberculosis arthritis according to biopsy and PCR TB result. Biopsy excision of the left kneefound granulomatous appearance, which is consistent with tuberculosis, PCR TB examination also found apositive effect. Antituberculosis treatment was started and will be continued for nine months. Tuberculosisarthritis frequently mimics more common etiologies and can be difficult to diagnose. Tuberculosis arthritismay be suspected in a chronic case of joint pain, usually monoarticular, although pulmonary TB may absent.